PENGGUNAAN ONOMATOPE PADA NOVEL MUSHOKU TENSEI: ISEKAI ITTARA HONKI DASU - Martia Irfianti; Hermandra Hermandra; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstarct: Comunication deliveries sentences and also sound imitation. Sound imitation or onomatopoeia can be found in oral/spoken language and written language. In a sentence, onomatopoeia has variations of type and gramatica function. This study aims to describe the types of phonology structure and gramatica functions of the onomatopoeia found on novel Mushoku Tensei: Isekai Ittara Honki Dasu. The onomatopoeia found on the sentences of the novel was chosen as the data of this study. The theory used in this study are the types of onomatope theory by Akimoto (2002), the part of speech theory by Murakami (1986), and the technique of lesap theory by Sudaryanto (1993) with descriptive-qualitative method. The result after the data has been analysed, six types of onomatopoeia on this novel are found chouon (long vowel), sokuon (dental consonant), hanpukukei (reduplication), hatsuon (nasal), double onomatopoeia, and suffix ri. Then, five types of gramatica functios are found verb, adjective, noun, adverb, and phrase. Then, new development was found, onomatopoeia is able to be removed if the predicate of the sentence is present and unable to be removed if the predicate of the sentence is missing.Key Words: Onomatopoeia, novel,sentences